Prevalence and variables associated with pediculosis capitis in kindergarten children from Popayán, Colombia (2017)
Introduction: Pediculosis capitis is a skin disease that affects the hair and scalp, and is caused by the Pediculus humanus capitis ectoparasite. High levels of infestation are reported worldwide, affecting especially children.Objectives: To determine the prevalence and the variables that are associated with pediculosis capitis in kindergarten children in Popayán, Colombia.Materials and methods: Cross-sectional descriptive study based on a sample of 148 children aged between 1 and 5 years of age. Only the head was examined. Nits, nymphs and adult lice were mechanically removed using lice combs and wetting the hair, covering the frontotemporal, parietooccipital, mastoid and nuchal regions. An informed consent and a structured survey were filled out by each parent or guardian.Results: The prevalence of pediculosis capitis in the studied population was 11.5%. The variables associated with ectoparasitosis were female sex, long hair (3 cm) and scalp pruritus.Conclusions: Pediculosis capitis is present and perpetuated in children from Popayán. Promotion, prevention and pediculicide treatment campaigns are strongly recommended.